2020
DOI: 10.3390/antibiotics9070371
|View full text |Cite
|
Sign up to set email alerts
|

Tackling Intrinsic Antibiotic Resistance in Serratia marcescens with a Combination of Ampicillin/Sulbactam and Phage SALSA

Abstract: During the antibiotic crisis, bacteriophages (briefly phages) are increasingly considered as potential antimicrobial pillars for the treatment of infectious diseases. Apart from acquired drug resistance, treatment options are additionally hampered by intrinsic, chromosomal-encoded resistance. For instance, the chromosomal ampC gene encoding for the AmpC-type β-lactamases is typically present in a number of nosocomial pathogens, including S. marcescens. In this study, phage SALSA (vB_SmaP-SALSA), with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…The dynamics of phage-or antibiotic-based challenges on bacterial populations were determined via measurements of the changes in optical densities (OD 590 ), which is particularly suited for high throughput analysis [32][33][34]. According to our previous studies, the presence of a β-lactam antibiotic does not interfere with the optical density values, which correlated with the reduction of bacterial cells rather than with altered cell morphology [14,15].…”
Section: Time-kill Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamics of phage-or antibiotic-based challenges on bacterial populations were determined via measurements of the changes in optical densities (OD 590 ), which is particularly suited for high throughput analysis [32][33][34]. According to our previous studies, the presence of a β-lactam antibiotic does not interfere with the optical density values, which correlated with the reduction of bacterial cells rather than with altered cell morphology [14,15].…”
Section: Time-kill Assaysmentioning
confidence: 99%
“…A number of studies have already addressed the potential impact of a dual approach against S. aureus using a lytic phage in combination with MRSA-effective antibiotics, such as rifampicin, linezolid, fosfomycin, daptomycin, and vancomycin [7][8][9][10][11][12][13], as well as in combination with aminoglycosides, quinolone antibiotics, and β-lactam antibiotics [5,[11][12][13]. Interestingly, synergistic interactions between a phage and an antibiotic can also be observed in cases in which the pathogen is resistant against the antibiotic [14,15]. However, combining a phage with an antibiotic, which as a sole agent does not work against MRSA, has not been investigated thus far.…”
Section: Introductionmentioning
confidence: 99%
“…In 2004, Huff et al assessed the therapeutic efficacy of using phages and enrofloxacin separately and in combination for the treatment of E. coli infections; they concluded that the phage–enrofloxacin combination was the most effective treatment [ 63 ]. In their 2020 study, Weber et al showed the utility of adding phage SALSA to ampicillin/sulbactam for the control of intrinsic Serratia marcescens resistance [ 59 ]. Other Gram-negative bacteria with intrinsic resistance to antibiotics, namely Burkholderia cepacia , Achromobacter spp.…”
Section: Examples Of Synergistic Phage–antibiotic Combinationsmentioning
confidence: 99%
“…Serratia marcescens is a Gram-negative bacterium of environmental origin like soil, water, and plant surfaces and known to be a plant as well as a human pathogen causing opportunistic infections in hospitals [1]. Serratia marcescens is still an underestimated bacterium that causes a range of infections in severely immunocompromised or critically ill patients with keratitis, conjunctivitis, urinary tract in-fections, pneumonia, surgical wound infections, sepsis, bloodstream infection, and menin gitis [2]. Considering that bacterial resistance to antibiotics increases, phages are one of the most promising alternatives that have to be applied [3].…”
Section: Introductionmentioning
confidence: 99%